DESIGN AND IN VITRO RELEASE KINETICS OF LIPOSOMAL FORMULATION OF ACYCLOVIR - ROY, DEBATRI; DAS, SUDIPTA; SAMANTA, ARNAB (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to formulate and evaluate liposomes loaded with acyclovir. Methods: Liposomal formulation of acyclovir was prepared by “thin lipid film method”. Mixture of phosphotidyl choline (soya lecithin), acyclovir and cholesterol of varying weight ratio was used for the preparation of liposomes. Total nine batches were prepared and each batch was prepared in triplicate. All batches were evaluated by drug entrapment and release kinetic studies. Stability study was carried out with F4 batch. Results: F2 and F9formulations showed better drug entrapment efficiency compared to the other batches. The drug entrapment efficiency of all batches was found within the range of 51.42 % to 79.0 %. F4 shows highest release of about 79.0% in 4 h. F4 formulation was found to follow significantly zero-order release kinetics. Short term stability study of formulation F4 showed no significant change in release kinetics. Conclusion: The F4 batches showed promising results compared to other formulations. No changes were founded during the short-term stability study of F4.